THE ROLE OF MECHANICAL ENGINEERING IN ECONOMIC DEVELOPMENT: CONTRIBUTIONS, INNOVATIONS AND FUTURE PROSPECTS - Nasriddinov Azizbek G‘anisher o‘g‘li (TADQIQOTLAR, 2025)
Abstract:  Mechanical  engineering  plays  a  pivotal  role  in  the  economic development  of  nations  by  driving  advancements  in  manufacturing,  infrastructure, innovation,  and  employment  generation.  This  paper  examines  the  contributions  of mechanical  engineering  to  various  industries, highlighting  its  impact  on  industrial growth,  technological  progress,  and  sustainability.  The  study  discusses  key innovations  such  as  automation,  robotics,  renewable  energy,  and  nanotechnology, which enhance productivity and economic stability. Additionally, the paper explores the  importance  of  education,  government  policies,  and  research  investments  in fostering a robust mechanical engineering sector. Despite challenges such as global competition  and  resource  constraints,  future  trends  in  artificial  intelligence,  smart manufacturing,  and  sustainable  engineering  practices  are  expected  to  further strengthen the sector's role in economic progress.